Relationship between Vitality and Characteristics of Coping Strategies in Deviant Adolescents - Chukhrova, Marina; Shchukina, Elena; Lavrinenko, Olga; Efremova, Ekaterina; Makarikhina, Inna (Journal of Ecohumanism, 2024)
Adolescence is important in the development and formation of a personality, and the family radically influences the development of a teenager; under the family influence, foundations of intentional behavior, ways of responding to stress, level of vitality and defense mechanisms are laid, and a general direction in the formation of moral concepts and relationships emerges. And all this happens against the background of contradictions in physiological and mental development, spiritual formation. The reasons for the use of psychoactive drugs are varied, and most often chemical dependence is determined by the combined action of various factors and conditions. The purpose of the research work was to study the relationship between family structure and characteristics of the adolescents’ response to stress in undergoing inpatient treatment due to the use of psychoactive substances. The study was conducted on the basis of the Novosibirsk Regional Clinical Narcological Dispensary (teenage department). The main group included 18 young men, age: from 15 to 18 years, with experience of using psychoactive substances from one year to three or more years - “teenage addicts”. The control group, “conditionally healthy”, denying the use of psychoactive substances, was represented by high school students of one of the gymnasiums, 15 young men of the same age group. The following methods were used: the Family Adaptation and Cohesion Scale (FACES-3) questionnaire; Plutchik, Kellerman, Conte questionnaire - Life Style Index (LSI) methodology; questionnaire “Methods of coping behavior” by R. Lazarus and S. Folkman and test of vitality (S. Muddy) adapted by D.A. Leontyev. Results. It was revealed that adolescent addicts differ from adolescents without addictive behavior in the following parameters: low level of family adaptation and family cohesion; Adolescents with addictive behavior differ in their style of responding to difficult life situations: they more often use defenses and coping, which serve the function of regulating negative emotional states associated with unmet needs for communication, self-affirmation, etc., while adolescents without addictive behavior use coping and defense, which main function is to resolve the situation; Adolescents with addictive behavior have a lower level of resilience than relatively healthy adolescents. The possibilities of psychotherapeutic influences are discussed.